Modeling the influence of an electric thruster’s ion beam on its global EMC - Rover, Yannik; Thueringer, Rainer; Probst, Uwe; Volkmar, Chris (Frontiers in Space Technologies, 2023)
The present work deals with electromagnetic compatibility (EMC) investigations in the field of electric propulsion (EP). To complete previous investigations, the emissions of of a fully operating radio-frequency thruster (RIT) -including its extracted ion beam -are analyzed numerically. The ion beam is simulated and investigated with various characteristics. The simulations are performed by means of a transient co-simulation. It becomes clear that the ion beam has a significant impact on the thruster emissions. Properties such as divergence angle and conductivity of the beam, which can directly be attributed to the operating point of the plasma discharge inside the thruster, play a major role. The next steps are to bring together all the knowledge gained about the emissions of the individual thruster components as well as the peripheral electronics.